Cytoprotective Effects of Pancreatic Cells of Interleukin 1 Inhibitors (DIACEREIN) on Glucose Homeostasis and Beta Cell in Diabetic Rat Model - Roomi Memon, Shagufta Memon, Farzana Memon, Naila Noor, Kiran Shaikh, Bushra Sajid Kazi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study was conducted to evaluate the pancreatic cells regeneration with interleukin 1 inhibitor drugs (diacerein) of natural source. Material & Methods: This experimental study was conducted at the Isra University animal house in which 60 albino rats were divided into 4 subgroups of 10 in each. Experimental group of them given alloxan and induced diabetes. interleukin 1 inhibitor (diacerein) was given to 2 experimental groups, diabetic experimental C and D respectively, in dosages of 30 mg/kg and 50 mg/kg for 21 days. After the completion of the experiment, rats were sacrificed by cervical dislocation. The pancreas of rats was removed and set in 10% formalin for fixation after being washed with normal saline. For appropriate fixation, the slides were placed on a hot plate. Hematoxylin and eosin were used to stain the slides, and under the light microscope, stained slides were examined. The study proforma was used to document all of the data. Results: Diabetic rats showed sustained hyperglycemia, total destruction of beta cells histologically. However, diabetic group rats showed degenerative changes of the pancreatic characterized by ultra-structural changes, shrinkage of beta islet cells, and showing RBCs and fibrosis of regions of endocrine glandular epithelial cells. Beta cells were showing mild regeneration with proliferative changes in the beta cells of islets as well as dilatation of ducts seen in treated groups with interleukin 1 inhibitor with lab findings of improving to euglycemic levels. Conclusions: Pancreatic tissue of diabetic rats showed ultra-structural changes and regeneration, as well as reduction in inflammatory markers as well as obvious effects on D.M., hence would be used as a cheap, safe drug to control and reduce the oxidative injury of pancreatic cells and its regenerative effects.